Can we predict failure in licensure exams from medical students’ undergraduate academic performance? - Desy, Janeve; Coderre, Sylvian; Veale, Pamela; Busche, Kevin; Woloschuk, Wayne; McLaughlin, Kevin (Canadian Medical Education Journal, 2021)
Background: In 2015, the Medical Council of Canada increased the minimum pass level for the Medical Council of Canada Qualifying Examination Part I, and students had a higher rate of failure than in previous years. The purpose of this study was to predict students at an increased odds of examination failure to allow for early, targeted interventions. Methods: We divided our dataset into a derivation cohort and two validation cohorts and used multiple logistic regression to predict licensing examination failure. We then performed receiver operating characteristics and a sensitivity analysis using different cutoffs for explanatory variables to identify the cutoff threshold with the best predictive value at identifying students at increased odds of failure. Results: After multivariate analysis, only pre-clerkship GPA was a significant independent predictor of failure (OR 0.76, 95% CI [0.66, 0.88], p < 0.001). The probability of failure increased steeply when the pre-clerkship GPA fell below 80% and 76% was found to be the most efficient cutoff for predicting failure (OR 9.37, 95% CI [3.08, 38.41]). Conclusions: Pre-clerkship performance can predict students at increased odds of licensing examination failure. Further studies are needed to explore whether early interventions for at-risk students alter their examination performance.